Organizational accommodation of employee mental health conditions and unintended stigma. Issue 15 (22nd August 2021) - Kalfa, Senia; Branicki, Layla; Brammer, Stephen
Abstract: Despite the growth in the severity and incidence of mental health conditions (MHCs) in wider society and within workplaces, relatively little research has focused on how organizations accommodate employees' MHCs, and how different approaches to accommodating MHCs contribute to their stigmatization. Drawing on in-depth interviews with HR managers from a variety of organizational contexts in Australia, our findings show that approaches to accommodating MHCs vary systematically across organizations, and that common approaches to accommodating employees with MHCs unintentionally stigmatize both employees with MHCs, and MHCs more generally. We identify two new forms of structural stigma, which we respectively label business-based structural stigma and care-based structural stigma, that stem from transactional and paternalist approaches to accommodating employees' MHCs. We explore the implications for de-stigmatizing MHCs in workplaces and for future HRM research that advances understanding of how organizations can better support employees with MHCs.